Urine volume dependency of specific dehydroepiandrosterone (DHEA) and cortisol metabolites in healthy children - Shi, Lijie; Wudy, Stefan A.; Maser-Gluth, Christiane; Hartmann, Michaela F.; Remer, Thomas (Steroids, 2011)
Urine volume should be considered as a confounder when using urinary free cortisol (UFF) and cortisone (UFE) to assess glucocorticoid (GC) status. We aimed to examine whether adrenal androgen (AA) metabolites may be also affected by urine volume in healthy children. To compare the flow dependence of GC and AA metabolites, specific GC metabolites were examined. In 24-h urine samples of 120 (60 boys) healthy children (4-10 yr), steroid profiles were determined by GC-MS analysis, UFF and UFE by radioimmunoassay. To assess daily AA and GC secretion rates, 7 quantitatively most important AA (∑C19) and GC (∑C21) metabolites were summed. Sum of DHEA and its 16α-hydroxylated metabolites were denoted as DHEA&M. Association of urine volume with AA (∑C19, DHEA&M, DHEA, 16α-hydroxy-DHEA, 3β,16α,17β-androstenetriol) and GC (∑C21, UFF, UFE, 6β-hydroxycortisol, 20α-dihydrocortisol) were examined in linear regression models. Among the examined AA metabolites, 16α-hydroxy-DHEA (β=0.56, p<0.0001) and DHEA (β=0.43, p=0.05) showed relatively strong association with urine volume. A trend was seen for ∑C19 (β=0.23, p=0.08), but not for DHEA&M (p>0.1). Regarding GC metabolites, urine volume showed a stronger association with cortisol's direct metabolites, i.e., cortisone, 6β-hydroxycortisol and 20α-dihydrocortisol (β=0.4-0.6, p<0.01) than with cortisol itself (β=0.28, p<0.05). ∑C21 was not associated with urine volume. In conclusion, like UFF and UFE, renal excretion of DHEA, 16α-hydroxy-DHEA, 6β-hydroxycortisol, and 20α-dihydrocortisol may also depend on urine volume. The intrarenal production of the latter three and cortisone might explain their relative strong water-flow-dependency. Total AA or GC secretion marker appears not to be relevantly confounded by urine volume.